Blended Lifelong Learning: A Practitioner's Approach - Athanasios Apostolopoulos (LED Edizioni Universitarie, 2014)
This paper reports on the various theories of blended learning and student interaction with emphasis given to lifelong/adult learning. In our application, we assess the interaction elements established in Anderson and Miyazoe, and namely that teacher-student interaction takes precedent in skill-based training. Our empirical case study also largely corroborates most of the claims made by Knowles' andragogy concept. We demonstrate that technology itself can never be a substitute for sound teaching, but it can become a tremendous tool in designing and implementing a variety of previously unattainable strategies and courses within the existing natural constraints of online or blended learning. In addition, applications depend heavily not just on technical considerations and support, but on the contextsubject, the actors involved (tutors, students and support stuff ) and the ability of all the parties involved to adapt in a timely fashion to unforeseen challenges in synchronicity. On the whole, it seems that by its very nature, blended learning is well suited to mature students since they are likely to be influenced by time and cost constraints while they have the personal motivation and experience necessary to be able to make constructive suggestions for improvements to a given course or curriculum.